Sistem Monitoring Kesehatan Udara menggunakan Sensor MQ7 dan MQ135 terhadap Berbagai Gas Berbahaya pada Mobil - Muhammad Zidni; Mochammad Hannats Hanafi Ichsan; Sabriansyah Rizqika Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Air is one of the important elements that support the daily routine of everything on this earth, but in today's time air quality is undergoing an undeniable shift in path due to extremely high levels of contamination, so the need for clean and natural air is right. -true is almost difficult to obtain in line with the rapid development of urban development, industry, and the high level of emission of motor vehicle emissions. Many cases of sudden death caused by this gas, especially in users of four-wheeled vehicles. Exhaust gas in vehicles is the residue from combustion in the form of water (H2O), Carbon Monoxide (CO), Carbon Dioxide (CO2), Nitrogen Oxide (NOx), Sulfur Dioxide (SO2) and Hydrated Carbon (HC) compounds as imperfections in the combustion process. and loose particles. To avoid this, a thesis is made to detect and monitor the presence of CO and CO2 gases in the air and any changes in the data detected by the sensors on the air health monitoring tool in the car will be stored, so that data on the presence of gas detected can be processed. and displayed as information. The implementation of the system uses two sensors as input, and if the sensor reads the parameter value, ESP32 will process the data and then the data is processed to be displayed on the web server. Then the data that has been inputted will be sent using the notification delivery protocol from the BOT telegram. From the results of testing the time of sending this data, the average time when the sensor sends data to the user gets a delivery time of 2566.66 ms (milliseconds) and vice versa, when the user takes data from the sensor, the average delivery time is 2766.66, this indicates if the data is sent fairly quickly also get satisfactory results.